The interplay of microRNA and neuronal activity in health and disease - Eacker, Stephen M.; Dawson, Ted M.; Dawson, Valina L. (Frontiers in Cellular Neuroscience, 2013)
MicroRNA (miRNA) are small 19-23nt regulatory RNAs that function by modulating mRNA translation and/or turnover in a sequence-specific fashion. In the nervous system, miRNA regulate the production of numerous proteins involved in synaptic transmission. In turn neuronal activity can regulate the production and turnover of miRNA through a variety of mechanisms. In this way, miRNAs and neuronal activity are in a reciprocal homeostatic relationship that balances neuronal function. MiRNA function is critical in pathological states related to over-excitation such as epilepsy and stroke, suggesting miRNA’s potential as a therapeutic target. We review the current literature relating the interplay of miRNA and neuronal activity and provide future directions for defining miRNA’s role in disease.